Flipped Classroom: Impact on Student Engagement among First-Year Management Undergraduates at the Open University of Sri Lanka - A. M. Upananda; D. R. P. Upananda (OUSL Journal)
In the 21st century, every corner of our lives is filled with digitalized technologies, which we cannot bypass. The educational landscape is also embarking on novel technology. Both learners and teachers should understand the novel technological paradigms, vise-versa to get a win-win situation. The flipped classroom is a pedagogical model in which traditional lecture and homework elements of a course are reversed. When looking at the Sri Lankan context, it is important to investigate whether we are adopting this novel teaching and learning paradigm. The recent literature lacks empirical investigations on the impact of the flipped model on student engagement, specifically in the Sri Lankan context. Hence, this study keeps a keen eye on the impact of the flipped classroom method on students’ engagement. As a leading state university whose foundation lays upon open and distance learning, the flipped classroom method is inherently practiced with the students. Therefore, a sample was drawn from the Open University of Sri Lanka, Faculty of Management Studies, using the convenience sampling technique. The participants were undergraduates who took the Principles of Management course in their first year. Researchers’ main investigation was to find the impact of the flipped model on student engagement. Therefore, behavioural responses and perceptions of students were considered as foremost factors, and therefore, a purely qualitative study was undertaken. In order to collect data, semi-structured interviews, self-administered questionnaires, and direct observations were used. Moreover, student engagement was investigated in terms of behavioural, cognitive, and emotional aspects. The collected data were analyzed using thematic analysis. Findings revealed that the flipped classroom method is an innovative teaching and learning method that can be effectively implemented to boost student engagement. In conclusion, the study highlighted the positive influence of the flipped classroom model on enhancing student engagement across behavioural, cognitive, and emotional dimensions. These findings underscored the potential of this learner-centered approach to transform traditional teaching practices within the Sri Lankan higher education context.